The Use of Robot-Assisted Gait Training (RAGT) to Improve Walking Independence in Stroke Rehabilitation: A Systematic Review - Fadya, Vannisa; Amira Qisthy Nabila; Ardia Mirati Alsandi (Acta Neurologica Indonesia, 2025)
Globally, stroke is the second leading cause of death and third in causing disability, although mortality rates have declined due to treatment advancements. This has led to an increased population of stroke survivors, with over 70% facing long-term motor, sensory, cognitive, or speech impairments, placing a substantial burden on families and society. Gait training plays a crucial role in enhancing daily living activities and independence. Currently, therapist-assisted rehabilitation is the primary approach, though it can be time-intensive and may lead to low adherence. However, technology is developing significantly in stroke rehabilitation with high-intensity, repetitive movements, potentially enhancing recovery. Therefore, current study aimed to conduct a systematic review of RCTs assessing the effectiveness of RAGT to improve walking independence. The outcome was the assessment of lower limb function using scales, such as the FAC, FMA-LE, and 6MWT. A thorough search was conducted in three databases. The risk for bias was evaluated using the Revised Tool RoB 2.0. There are inconsistent findings in the effectiveness of RAGT in improving motor function, walking ability, and walking endurance compared to conventional. But, RAGT showed promising results, particulary in the subacute phase. Peak neurologic recovery of stroke occurs within 1–3 months after the onset of stroke. From this time to 6 months, recovery slows down. In conclusion, the use of RAGT in stroke rehabilitation yielded a favorable and promising outcomes. However, the effectiveness compared to conventional therapy has not yet been consistently significant.